2012
DOI: 10.3747/pdi.2010.00234
|View full text |Cite
|
Sign up to set email alerts
|

Peritoneal Morphology after Long-Term Peritoneal Dialysis with Biocompatible Fluid: Recent Clinical Practice in Japan

Abstract: ♦ Background: Morphology changes of the peritoneal membrane after long-term peritoneal dialysis (PD) consist of denudation of peritoneal mesothelial cells, interstitial sclerosis, and hyalinizing vasculopathy. Those changes are considered to be the result of uremia and bioincompatible effects of conventional acidic lactate-buffered dialysate with glucose degradation products (GDPs). In the last decade, biocompatible dialysate with neutral pH and low GDPs has become widely used. Clinical practice has been modif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
39
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(40 citation statements)
references
References 39 publications
1
39
0
Order By: Relevance
“…Unlike PD duration, the type of PD solutions received exerted no significant effect on the trend of dialysate MMP-2 or TIMP-1 concentrations. This was an unexpected outcome because the use of biocompatible solutions has been associated with an improvement in peritoneal membrane morphology (22). Similarly, an observational study reported a significant decrease in both PD effluent MMP-2 levels (141.4 ± 52.5 to 91.3 ± 15.1 ng/mL; p < 0.05) and PSTR (D:P Cr4h 0.72 ± 0.09 to 0.60 ± 0.06; p < 0.03) in prevalent PD patients (mean PD duration 44.6 months) when their treatments were switched from standard solutions to biocompatible solutions (14).…”
Section: Discussionmentioning
confidence: 99%
“…Unlike PD duration, the type of PD solutions received exerted no significant effect on the trend of dialysate MMP-2 or TIMP-1 concentrations. This was an unexpected outcome because the use of biocompatible solutions has been associated with an improvement in peritoneal membrane morphology (22). Similarly, an observational study reported a significant decrease in both PD effluent MMP-2 levels (141.4 ± 52.5 to 91.3 ± 15.1 ng/mL; p < 0.05) and PSTR (D:P Cr4h 0.72 ± 0.09 to 0.60 ± 0.06; p < 0.03) in prevalent PD patients (mean PD duration 44.6 months) when their treatments were switched from standard solutions to biocompatible solutions (14).…”
Section: Discussionmentioning
confidence: 99%
“…However, this phenomenon was not observed in the present cohort that was treated with neutral-pH solution. Recent studies suggest that the use of neutral solutions is associated with improved mesothelial layer integrity, decreased thickening of the submesothelial compact zone, and less vasculopathy when compared with those that occur in response to conventional acid solutions (31)(32)(33). These observations suggest that this newer solution might help attenuate the risk of EPS.…”
Section: Discussionmentioning
confidence: 99%
“…The use of PD solutions that are more biocompatible, with a neutral pH and reduced levels of glucose degradation products (GDPs), might lower the systemic inflammatory burden by improving peritoneal membrane morphology (4,5); better preserving cellular host defenses (6), leading to a milder physician-rated severity of peritonitis (7); and better preserving RRF (8).…”
mentioning
confidence: 99%